2022
DOI: 10.1177/07334648221130747
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Script of Work-Related Burdens in Home Care – A Cross Over Mixed Analysis of Audio Diaries

Abstract: The lived experiences of work-related burdens in the daily working routines of home care workers are insufficiently investigated. Therefore, the aim of this study is to examine the types, frequencies, and distributions of work-related burdens and to explore their co-occurrence. Qualitative data was collected via audio diaries and analyzed applying a crossover mixed analysis using content as well as network analysis. In all, 23 home care workers (mean age = 46.70 ± 10.40; 91.30% female) produced 242 diary entri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Personal safety and wellbeing: The physical and emotional nature of the work, lack of safety and support systems, as well as individual client and worker characteristics, contribute to work-related burden in home support work impacting job satisfaction and retention ( 204 211 ). Client behaviours in the home, such as occupational tobacco smoke exposure, can create significant health challenges for HSWs, requiring standard terms and agreements to be put in place with clients and families to safeguard employees ( 212 ).…”
Section: Resultsmentioning
confidence: 99%
“…Personal safety and wellbeing: The physical and emotional nature of the work, lack of safety and support systems, as well as individual client and worker characteristics, contribute to work-related burden in home support work impacting job satisfaction and retention ( 204 211 ). Client behaviours in the home, such as occupational tobacco smoke exposure, can create significant health challenges for HSWs, requiring standard terms and agreements to be put in place with clients and families to safeguard employees ( 212 ).…”
Section: Resultsmentioning
confidence: 99%
“…Physical parameters dominate the endpoints of included studies, indicating a still predominant biomedical perspective on health. Since psychosocial and mental demands characterize everyday work in home care (Grasmo et al, 2021; Ruotsalainen et al, 2020) and are reported as burdening much more frequently than physical strains (Gebhard & Wimmer, 2022), interventions must broaden their approach to a biopsychosocial perspective. A review indicated that mindfulness trainings have a positive effect on the mental health of nurses (Guillaumie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a wide range of health-damaging factors associated with home care work. Home care workers experience burdens most frequently related to work organization (Gebhard & Wimmer, 2022; Sjöberg et al, 2020), including staffing challenges, too tight schedules (Mojtahedzadeh et al, 2021a; Ruotsalainen et al, 2020), and the requirement to perform additional tasks on a daily basis (Karlsson et al, 2020). These conditions result in high workloads and time pressure (Fjørtoft et al, 2020; Grasmo et al, 2021; Otto et al, 2019; Sjöberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, Finland is a fitting country to study how to meet care challenges that arise from aging populations. Recent studies conducted in home care have demonstrated problems among caregivers, with time pressure and stress as well as dissatisfaction and turnover intentions being prevalent (Gebhard & Wimmer 2023 ; Ruotsalainen et al 2020 ). Furthermore, demands for high efficiency, and insufficient number of nurses can result in increasingly intense workdays, which might lead to strain, poor recovery, and sickness absences.…”
Section: Introductionmentioning
confidence: 99%